2015
DOI: 10.1016/j.jcma.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Improved assay performance of single nucleotide polymorphism array over conventional karyotyping in analyzing products of conception

Abstract: This study demonstrated that SNP array had certain advantages over G-banded karyotyping, including a higher success rate, additional detection of copy number variations and uniparental disomy, and improved sensitivity to mosaicism. Therefore, it would be an alternative method to karyotyping in clinical genetic practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 24 publications
5
29
0
Order By: Relevance
“…Previous studies have shown that TBX20 polymorphisms are closely related to the occurrence and development of CHD in children Kwiatkowski et al, 2015;Lin et al, 2015;Monroy-Muñoz et al, 2015), results of this study were in concordance with those of previous studies. TBX20 SNP loci that have been reported thus far include: rs6950175 and rs3999941.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that TBX20 polymorphisms are closely related to the occurrence and development of CHD in children Kwiatkowski et al, 2015;Lin et al, 2015;Monroy-Muñoz et al, 2015), results of this study were in concordance with those of previous studies. TBX20 SNP loci that have been reported thus far include: rs6950175 and rs3999941.…”
Section: Discussionsupporting
confidence: 93%
“…The evaluation of single nucleotide polymorphisms (SNP) is a key approach to explore and identify genetic predispositions to a certain condition (Lin et al, 2015), particularly for polygenic disease research (Kwiatkowski et al, 2015;Knopp et al, 2015). Through the study of SNPs in predisposing genes, the relationship between the gene and the disease can be clarified, which is of significant value for disease diagnosis, treatment, and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…3 SNP combing across the genome (approximately 1/10 kb) with an informatics technique is used to detect gains and losses and identifies maternal cell contamination, triploidy, and uniparental disomy. 4 In this issue, Lin et al 5 have authored an interesting article entitled Improved assay performance of single nucleotide polymorphism array over conventional karyotyping in analyzing products of conception. We heartily applaud the publication of this article, because the diagnoses were consistent with previous reports based on traditional cell culture and karyotyping of products of conception.…”
mentioning
confidence: 99%
“…SNP array not only demonstrated a higher success rate for detecting chromosomal abnormalities (98.1% vs. 85.8%), but also provided an additional ability to detect pathologic copy number variations and whole-genome uniparental disomy (UPD) compared with conventional karyotyping (G-banded karyotyping), thus contributing to a higher detection rate of abnormalities (62.6% vs. 61.3%). 5 Furthermore, the use of SNPs also significantly improved sensitivity to mosaicism. 5 By contrast, two cases of chromosome translocation and one case of tetraploidy were not detected by SNP but by conventional karyotyping.…”
mentioning
confidence: 99%
See 1 more Smart Citation